EFEKTIFITAS PENGGUNAAN MEDIA YOUTOBE TERHADAP HASIL BELAJAR MATEMATIKA SMP NEGERI 2 PAREPARE - Nirmalasari Nirmalasari (Tautologi: Journal of Mathematics Education, 2024)
This research aims to determine the effectiveness of using the YouTube application in mathematics learning for class VIII UPTD students at SMP Negeri 2 Parepare. This type of research is Pre-Experimental. The sample for this research was students of class VIII UPTD SMP Negeri 2 Parepare in the odd semester of the 2021/2022 academic year using a sampling technique, namely cluster random sampling. Data collection was carried out using research instruments in the form of test sheets, student activity observation sheets, teacher ability observation sheets to manage learning and student response questionnaire sheets. The results of the research show that learning using YouTube media is effective in mathematics learning for class VIII students at UPTD SMPN 2 Parepare. This is shown by descriptive analysis, namely (1) student learning completeness is included in the "High" category with an average score of 87,038 where classically 100% of students have completed it, (2) student activities are in accordance with learning using YouTube media The average percentage obtained was 60.42% or in the "Good" category, (3) the average score for teacher ability in managing learning was 4.14 and included in the "Good" category and (4) the students' response to learning mathematics using YouTube media was very positive with an average of 71.88%. Meanwhile, based on inferential analysis using the one sample t-test in the posttest, a significant value of p = 0.000 < α = 0.05 was obtained and the one sample t-test on the gain value obtained a significant value of p = 0.000 < α = 0.05 so it can be concluded that H_0 is rejected and H_1 accepted, which means that there is effectiveness in using YouTube media in mathematics learning for class VIII students at UPTD SMPN 2 Parepare